@Sophie, sorry for the late response, just got around to a piece of paper, and looks like you might have gotten what you were looking for? Anyway, this is too fun to pass up, and perhaps you should try to play with it yourself to get some more intuition.. the efficient way is to correspond your group to $S_3$ and see that the relationship indeed hold in $S_3$, but perhaps it's instructive (and certainly fun) to play with what you already have. So, you have
$a^2 = b^3 = (ab)^2 = e \iff a = a^{-1};\ b^2 = b^{-1};\ ab = (ab)^{-1} = b^{-1}a^{-1}$. Then I claim that the generated group is the fo…
$a^2 = b^3 = (ab)^2 = e \iff a = a^{-1};\ b^2 = b^{-1};\ ab = (ab)^{-1} = b^{-1}a^{-1}$. Then I claim that the generated group is the fo…